Final report on the simplification and harmonization of shipping documentation and procedures in the Caribbean Community (CEDP St. Michael, BarbadosBB, 1991)
Discusses issues arising out of presentations at workshop on the simplification/harmonization of shipping forms. Outlines schedule of activities towards the introduction of uniform shipping documentation. Annexes contain model forms, documentary requirements for ships at regional ports, recommendations on regional shipping documentation, and current developments in shipping documentation.
DC